2009
DOI: 10.5713/ajas.2009.80224
|View full text |Cite
|
Sign up to set email alerts
|

Bermuda Grass Hay or Sorghum Silage with or without Yeast Addition on Performance and Carcass Characteristics of Crossbred Young Bulls Finished in Feedlot

Abstract: This experiment was carried out to evaluate performance and carcass characteristics of 40 crossbred young bulls (Zebu×European) finished in a feedlot under two roughage sources (Bermuda grass hay or sorghum silage) with or without the addition of yeast (Saccharomyces cerevisae). The bulls were 20 months old, their initial average weight was 356 kg and they were allocated into four groups of ten animals. The experimental diets were Bermuda grass, Bermuda grass+yeast, sorghum silage and sorghum silage +yeast. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 31 publications
10
29
1
3
Order By: Relevance
“…According to Müller's scale (1980), the color for all genetic groups may be considered satisfactory, as they The mean rates of moisture, ashes and crude protein were 72.8, 1.03 and 22.7%, respectively. These results were similar to those found by Ducatti et al (2009) who evaluated chemical and fatty acids composition of different genetic groups (Purunã 1 st generation; Purunã 2 nd generation; Caracu; Canchin vs. Angus and Charolês vs. Caracu) and the mean values observed were 73.3, 0.97% and 22.5%, respectively. According to these results, moisture, ashes and crude protein rates did not show any variations owing to the genetic groups.…”
Section: Carcass Characteristicssupporting
confidence: 77%
See 2 more Smart Citations
“…According to Müller's scale (1980), the color for all genetic groups may be considered satisfactory, as they The mean rates of moisture, ashes and crude protein were 72.8, 1.03 and 22.7%, respectively. These results were similar to those found by Ducatti et al (2009) who evaluated chemical and fatty acids composition of different genetic groups (Purunã 1 st generation; Purunã 2 nd generation; Caracu; Canchin vs. Angus and Charolês vs. Caracu) and the mean values observed were 73.3, 0.97% and 22.5%, respectively. According to these results, moisture, ashes and crude protein rates did not show any variations owing to the genetic groups.…”
Section: Carcass Characteristicssupporting
confidence: 77%
“…According to these results, moisture, ashes and crude protein rates did not show any variations owing to the genetic groups. However, total lipids and total cholesterol rates reported by Ducatti et al (2009) were higher (2.16% and 42.0 mg 100 g -1 of muscle) than those in current analysis (1.37% and 36.6 mg 100 g -1 of muscle). Kazama et al (2008);Rotta et al (2009a and b) also reported higher total cholesterol rates when compared to those in current experiment.…”
Section: Carcass Characteristicscontrasting
confidence: 49%
See 1 more Smart Citation
“…Thus, due to increases in the consumption of beef and the demand for quality products by consumers in Brazil, finishing cattle in feedlots may be a tool to maximize production and improve meat quality (Prado et al ., 2008;Rotta et al ., 2009). In Brazil, bulls are finished in feedlots when they reach 380 Kg body weight (BW) at about 24 months of age (Maggioni et al ., 2009;. There has been an increase in using feedlot systems for finishing young bulls at 18 months (Dian et al ., 2010;Ito et al ., 2010) and bulls after weaning at 10 and 12 months of age (Ito et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The meat has important nutritional function on human diet by proteins with high quality (WEBB; O'NEIL, 2008), essential fatty acids (MOREIRA et al, 2003;KAZAMA et al, 2008;MACEDO et al, 2008;MAGGIONI et al, 2009;ROTTA et al, 2009a;, minerals and complex B vitamins. However, the consumption of red meat has been associated with health problems (cardio diseases, obesity, hypertension and cancers, WOOD et al, 2004) by presence of saturated fatty acids and cholesterol (KAZAMA et al, 2008;PRADO et al, 2009a;2009c).…”
Section: Introductionmentioning
confidence: 99%